Can traditional fermented food products protect mothers against lactational mastitis (Retraction of vol 15, Pg 163, 2020) - Basım, Pelin; Özdenkaya, Yaşar (Mary Ann Liebert Inc., 2021)
Breastfeeding Medicineofficially retracts the published article entitled, ‘‘Can Traditional Fermented Food ProductsProtect Mothers Against Lactational Mastitis,’’ by Pelin Basım and Yaşar Özdenkaya (Breastfeed Med 2020;15(3):163–169(doi: 10.1089/bfm.2019.0261).
Keywords: Lactational Mastitis; Fermented Food; Probiotics